2021
DOI: 10.4102/hsag.v26i0.1523
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’, nurses’ and clinical associates’ understanding of emergency care practitioners

Abstract: Background: Healthcare professionals’ understanding of the knowledge, skills and training of their counterparts from other disciplines cultivates appreciation and respect within the workplace. This, in turn, results in better teamwork and improved patient care. Emergency departments are places where emergency care practitioners (ECPs) engage with doctors, nurses and clinical associates. Whilst the importance of inter-professional communication and teamwork between in-hospital professionals and pre-hospital eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These circumstances are supported by other local studies that have shown that in-hospital staff generally have poor knowledge related to existing prehospital qualifications and scope of practice. [24,25] Consequently, hospitals commonly request CCTs for patients whose ongoing care and monitoring needs far exceed the scope and capability of the CCT team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These circumstances are supported by other local studies that have shown that in-hospital staff generally have poor knowledge related to existing prehospital qualifications and scope of practice. [24,25] Consequently, hospitals commonly request CCTs for patients whose ongoing care and monitoring needs far exceed the scope and capability of the CCT team.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the management of high-acuity patients in continually resource-constrained environments is linked to suboptimal patient care, compassion fatigue and interprofessional relationship strain. [25] While CCT plays a vital role in the resource-constrained healthcare system, the absence of a contextually relevant definition of what constitutes a CCT, coupled with potential curriculum deficits in undergraduate EC programmes, has a negative impact on the experiences of EC providers conducting CCTs. Acknowledging CCT as an area of specialisation is an important first step in addressing some of the frustrations and challenges experienced by EC providers tasked with conducting CCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Accurately sharing information is a key factor in sustaining safe patient care in the healthcare setting, and it is a priority to improve patient safety around the world (5). Clinical handoff provides advances in nursing services including promoted care, enriched care prioritization, increased transfer of patients' information to nurses, improved documentation, decreased overtime, reduced misinterpretations, and improved efficiency and teamwork (1,4,6,7). Herawati claimed that good handover assist in detecting mistakes and supporting the continuity of care (8).…”
Section: Introductionmentioning
confidence: 99%
“…Within the South African setting there have been a number of focused research initiatives aimed at improving pre-hospital care systems, however these initiatives have highlighted the need for further research into, and development of SA EMS systems and processes [6 , 7] . Mianda et al suggest there is an ongoing systemic lag in the development of clinical leadership competency among frontline healthcare providers, leading to slow professionalization of ‘non-physician’ based healthcare units [8] .…”
Section: Introductionmentioning
confidence: 99%